Monitoring changes in lower-limb strength and power in elite athletes with the countermovement-jump and Keiser leg-press tests - Nysether, S.; Hopkins, W. G.; Mentzoni, F.; Paulsen, G.; Haugen, T. A.; Solberg, P. A. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To determine the utility of countermovement-jump and Keiser leg-press tests for tracking changes in elite athletes of different sports.